2020
DOI: 10.1002/ange.202005563
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective S−H Insertion Reactions of α‐Carbonyl Sulfoxonium Ylides

Abstract: The first example of enantioselective S−H insertion reactions of sulfoxonium ylides is reported. Under the influence of thiourea catalysis, excellent levels of enantiocontrol (up to 95 % ee) and yields (up to 97 %) are achieved for 31 examples in S−H insertion reactions of aryl thiols and α‐carbonyl sulfoxonium ylides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The structure of 3 aa was confirmed by comparison its NMR spectra with literature. [16] Subsequent exploration of the two reactants' ratio suggested that 1 : 2.0 of 1 a:2 a was the best choice (entries 2-6). Higher yield was obtained from the excess use of 2 a.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of 3 aa was confirmed by comparison its NMR spectra with literature. [16] Subsequent exploration of the two reactants' ratio suggested that 1 : 2.0 of 1 a:2 a was the best choice (entries 2-6). Higher yield was obtained from the excess use of 2 a.…”
Section: Resultsmentioning
confidence: 99%
“…Activation energies (or activation barriers, used interchangeably here) can be evaluated by modeling reactions with quantum mechanical (QM) calculations, particularly density functional theory (DFT) 6,7 . DFT has played a major role in calculating activation energies of reactions in several valuable areas of chemistry including: mechanistic modeling of organic reactions, 8–12 drug design, 12–14 toxicology, 15,16 and catalyst design 17–19 . However, accurate QM and DFT calculations incur a significant computational expense 20–22 and their practicality for reaction modeling on a large scale is thus limited.…”
Section: Introductionmentioning
confidence: 99%
“…9 During the preparation of this article, Burtoloso and co-workers reported an elegant S−H insertion of arylthiols with α-ester sulfoxonium ylides by chiral thiourea catalysis, leading to a range of α-arylthio esters in 45−95% ee. 10 Notably, in contrast to the α-ester sulfur ylides, asymmetric insertion using α-keto sulfur ylides has not been realized. We envisioned that these reactions may remedy some of the drawbacks encountered with α-diazoketones.…”
Section: ■ Introductionmentioning
confidence: 99%